2020
DOI: 10.1590/1980-5918.033.ao35
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of functional mobility with handgrip strength, functional capacity for instrumental activities of daily living, fear of falling and number of falls in community-dwelling elderly

Abstract: Introduction: Functional mobility is essential for quality life and its worsening is the first sign of functional decline in the elderly. Objective: To assess the correlation of functional mobility with handgrip strength (HGS), functional capacity for IADL (FC-IADL) and fear of falling and number of falls in community-dwelling elderly. Method: A cross-sectional study was conducted with 303 community-dwelling elderly of both sexes, in Juiz de Fora (MG, Brazil). Functional mobility (TUG), HGS (dynamometer, JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As the balance and strength of the elderly are often compromised, their fear of falling increases constantly, limiting socialization and performance of DLAs, which generates a snowball effect of disuse and decreased function, muscle mass, balance, posture, coordination, and flexibility (30) . In addition to all the physical phenomena inherent in falls, these have psychic and social repercussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the balance and strength of the elderly are often compromised, their fear of falling increases constantly, limiting socialization and performance of DLAs, which generates a snowball effect of disuse and decreased function, muscle mass, balance, posture, coordination, and flexibility (30) . In addition to all the physical phenomena inherent in falls, these have psychic and social repercussions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all the physical phenomena inherent in falls, these have psychic and social repercussions. When feeling fear of falling, the person loses self-confidence, isolates himself, becomes more dependent on the performance of daily life activities, leading to greater dependence on third parties (30)(31)(32) .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of fear of falling (FoF) in the elderly is from 20% to 39% [4]. However, few studies have addressed the relationship between FoF, QoL, basic activities of daily living (ADL), and instrumental ADL in elderly women [3,5,6]. Directly, the FoF in the elderly can affect their QoL and also disrupt basic ADL and instrumental ADL in the elderly [7].…”
mentioning
confidence: 99%
“…However, previous evidence is limited in the field of the relationship between FoF, QoL, basic ADL, and instrumental ADL in elderly women [3,5,6]. Meanwhile, a study in Brazil showed that the FoF can affect basic ADL and instrumental ADL [5]. Another study in Norway showed that there is a high correlation between QoL, basic ADL, and instrumental ADL [6].…”
mentioning
confidence: 99%